Can Scholarships Increase High School Graduation Rates? Evidence from a Randomized Control Trial in Mexico - de Hoyos, Rafael; Attanasio, Orazio; Meghir, Costas (World Bank, Washington, DC, 2019)
This paper studies the impact of PROBEMS, a scholarship program in Mexico aimed at improving graduation rates and test scores among upper secondary school students from poor backgrounds. The identification strategy is the random allocation into the program, which took place in 2009. The strategy allows measurement of the effects of PROBEMS on test scores and graduation rates three years later in 2012. The paper finds that, on average, the program has no discernible impact on graduation rates or math or Spanish test scores. The size of the sample allows investigation of the reasons for this disappointing result. The paper finds that the program is substantially mis-targeted, with the majority of the recipients not coming from the most disadvantaged families. However, the most plausible explanation for the absence of positive impacts is that many eligible students do not seem to have the minimum learning level to face successfully the academic requirements of upper secondary school. An important policy implication is that a well-targeted scholarship program should be complemented with a remedial education intervention.